2020
DOI: 10.1186/s40478-020-01074-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglia infection by rabies virus after anterograde virus spread in peripheral neurons

Abstract: The highly neurotropic rabies virus (RABV) enters peripheral neurons at axon termini and requires long distance axonal transport and trans-synaptic spread between neurons for the infection of the central nervous system (CNS). Recent 3D imaging of field RABV-infected brains revealed a remarkably high proportion of infected astroglia, indicating that highly virulent field viruses are able to suppress astrocyte-mediated innate immune responses and virus elimination pathways. While fundamental for CNS invasion, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Additionally, viral antigen has been detected in the intestine of ferrets [ 31 ], hamsters [ 34 , 35 ], and rhesus macaques [ 44 ]. Previous studies with other viral pathogens demonstrated that volumetric 3D imaging using TOC and LSFM is a highly valuable tool to assess the comprehensive distribution of virus infection in vivo [ 51 , 54 ]. Additional immunostaining against tissue-specific cell markers may further facilitate the investigation of the global SARS-CoV-2 cell tropism in affected tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, viral antigen has been detected in the intestine of ferrets [ 31 ], hamsters [ 34 , 35 ], and rhesus macaques [ 44 ]. Previous studies with other viral pathogens demonstrated that volumetric 3D imaging using TOC and LSFM is a highly valuable tool to assess the comprehensive distribution of virus infection in vivo [ 51 , 54 ]. Additional immunostaining against tissue-specific cell markers may further facilitate the investigation of the global SARS-CoV-2 cell tropism in affected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This eliminates the need for physical sectioning and allows acquisition of intact three-dimensional (3D) structures using only optical sectioning, e.g., in light sheet fluorescence microscopy (LSFM) [ 50 ]. Lately, the opportunities and advantages of TOC for virus research have been demonstrated in several studies [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. While two approaches to 3D imaging of SARS-CoV-2-infected lung tissue have been described recently [ 58 , 59 ], neither of them is capable of direct visualization of SARS-CoV-2 infection via virus-specific antigen staining.…”
Section: Introductionmentioning
confidence: 99%
“…And then light-microscopy techniques can be used to access the entire mouse brain 27 . Recently, three-dimensional light sheet and confocal laser scanning microscopy was also applied to investigate the distribution of RABV in the brain and peripheral nerves 28 . fMOST technology makes it possible to map the spread of neurotropic viruses in the whole brain.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas most of the research is focussing on the discovery of RABV receptors (1)(2)(3)(4) and their interaction with the RABV G-protein (21), less research focusses on how cellular host immune responses shape RABV tropism and how the type of response of the different neural cell types present in the CNS could collectively lead to the establishment of an antiviral response. Recently, several publications reported infection of different glial cells in vivo, particularly astrocytes (27,28) and Schwann cells (9), depending on the viral strain and the infection route used (8). Still, we are far from understanding the molecular pathways underlying susceptibility to RABV infection although it is crucial in determining infection outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Several receptors are known to accelerate RABV entry to the cell (14) and yet, none of them seems to be essential for successful infection (5,6) questioning a marked cellular tropism. Although RABV is classically reported as strictly neurotropic (7), recent studies report profound infection of glial cells in vivo depending on the viral strain and the infection route used (8,9). Here, we provide evidence that human neural stem cell (hNSC)-derived neurons (hiNeurons) and astrocytes (hiAstrocytes) are highly susceptible towards infection with the virulent field RABV strain Tha and less virulent Th2P-4M.…”
mentioning
confidence: 99%